Faktor-Faktor yang Mempengaruhi Implementasi Kebijakan Dana Desa Pada Masa Pandemi COVID-19: Studi Kasus di Kecamatan Musi Kabupaten Timor Tengah Utara: Factors Influencing Implementation of Village Fund Policies During the COVID-19 Pandemic: A Case Study in Musi Sub-District, North Central Timor Regency - Yohanes Fritantus; Yoakim Rembu (Society, 2023)
The impact of the COVID-19 pandemic in Indonesia, including the existence of a Village Fund refocusing policy for handling COVID-19 that for the management of Village Funds for the 2021 fiscal year, a minimum of 8 percent and 40 percent of the Village Funds realized in each village must be focused on handling COVID-19 19. This study aimed to analyze and describe the factors that influenced the Village Government in Musi Sub-District, North Central Timor Regency, in implementing the Village Fund Refocusing and Reallocation Policy during the COVID-19 pandemic. Data was collected through observation, direct interviews with informants and searching archives and documents related to research. The results of the study concluded that the implementation of the Village Fund refocusing and reallocation policies had not been implemented optimally. Factors that cause it not to be optimal are understanding and mastery of information technology systems (Village Financial Systems) and the administrative requirements needed. Another obstacle is the overlapping laws and regulations regarding the refocusing and reallocating of Village Funds during the COVID-19 Pandemic.